Caracterização de práticas de melhoria contínua e seus impactos : estudo de caso em uma empresa de bens de consumo - Segundo, Ronaldo Aparecido (Universidade Federal de São Carlos, 2012)
Competitiveness of companies demands strategies that respond to competitive challenges in the organization. One way to address these challenges is related to Total Quality Management, in particular the continuous improvement of products, processes and management. In this way the literature shows some approaches and tools for the deployment of continuous improvement. Although it has been focused by several authors, the participation of people is still a critical factor for success in continuous improvement initiatives. But it was not fully evident in the literature the importance of collaboration and interaction of people during the programs and continuous improvement projects. As a result, the goal of this research is to investigate the importance of collaboration and interaction in the results and maintenance of continuous improvement programs. The research method it was a case study and the research was conducted in a consumer goods company with experience in implementing several programs of continuous improvement. Empirical evidence shows that the results and the maintaining continuous improvement programs are influenced by interaction and collaboration between individuals especially in the long term. This dissertation contributes to both organizational and for academia, for understanding the importance of interaction and collaboration between people can help correct the actions of organizational actors to better utilization of continuous improvement programs.
Keywords: Melhoria contínua; Competitividade; Gestão da qualidade total; Colaboração; Interação social, Integração; Total quality management; Continuous improvement; Innovation; Collaboration; Interaction; ENGENHARIAS::ENGENHARIA DE PRODUCAO